Overview of the use of rheumatic drugs with risk factors for rheumatism at puskesmas x Tanah Datar regency - Renatalia Fika; Yonrizon Yonrizon; Muhajri Agusfina; Mevy Trisna; Asih Permani Putri (Science Midwifery, 2023)
Arthritis (rheumatism) affects the joints and associated structures. Rheumatism, sometimes known as gout or aches & pains, is a common condition. Untreated pain can prolong the condition and harm the patient. Humans have taken many painkilling measures. So Puskesmas X Tanah Datar Regency's rheumatic drug consumption with risk variables was studied. Purposive sampling was used. Bivariate study examined Puskesmas X Tanah Datar Regency patient recurrence. 100 participants satisfied the inclusion criteria, 50 of whom relapsed and 50 who did not. Variables that influence the description of the use of rheumatic drugs with rheumatic risk factors at Puskesmas X Tanah Datar Regency are age (P. 0.069), gender (P. 0.046), occupation (P. 0.029), and obesity status (P.0.007). Factors that can raise the risk of rheumatism in the working area of ​​the PuskesmasXTanah Datar Districtare age, sex, occupation and obesity status (BMI). The drugs most widely used for the treatment of rheumatism in the working area of ​​the Puskesmas X Tanah Datar district is Na. Diclofenac.